The Influence Of Lifestyle, Celebrity Endorser, And Brand Awareness On Purchase Intention Instant Lemonilo Noodles Products In Jabodetabek - Yohanes Ferry Cahaya; lina basafira dewi (Management Research Studies Journal, 2022)
This study aims to determine the effect of Lifestyle, Celebrity Endorser, and Brand Awareness on Purchase Intention Lemonilo Instant Noodle Products. The research design used is causality research design while the type of research used is quantitative research using questionnaires. The research population is all people who are interested in and or like healthy instant food in Jabodetabek, while the sampling technique uses purposive sampling with a total of 100 respondents. The analytical tool used is SPSS version 26. The results of the analysis obtained are multiple linear regression analysis, partial analysis (t-test), regression model reliability analysis (f-test), correlation coefficient analysis, and coefficient of determination analysis. The results showed that: (1) Lifestyle had a positive and significant effect on Purchase intention and had the greatest influence; (2) Celebrity Endorser has a positive and significant effect on Purchase intention and has the least effect; (3) Brand Awareness has a positive and significant effect on Purchase intention and has a greater influence than Celebrity Endorser and less than Lifestyle. Reliability analysis of the regression model (f-test) shows that the regression model is considered feasible in explaining the independent variables. Analysis of the coefficient of determination (R2) shows that Lifestyle, Celebrity Endorser, and Brand Awareness contribute 59.6% to Purchase intention.